Rancang Bangun Spektroskopi FTIR (Fourier Transform Infrared) untuk Penentuan Kualitas Susu Sapi - Endro Suseno, Jatmiko; Firdausi, K. Sofjan (BERKALA FISIKA, 2008)
A Fourier Transform Infrared spectroscopy instrument has beed developed in the range middle infrared. The important instrument in this research is to make interferogram using He-Ne Laser based on Michelson interferometer. The result indicates that the interferogram seems work well and should give some spectra in the range of middle infrared frequencies. Key words: FTIR, interferogram, spectroscopy